THE TAPESTRE FRAMEWORK: EQUALISING AN UNEVEN GLOBAL KNOWLEDGE BASE TO INFORM RELEVANT, RESPONSIBLE AND RESPONSIVE EVIDENCE-BASED EDUCATION POLICY AND PRACTICE - Ebersöhn, Liesel; Murphy, Karen; Basson, Liz-Marié (Jornal de Políticas Educacionais, 2024)
The global knowledge base, which informs education policy and practice, is skewed – privileging evidence from the Global North and Eurocentric lenses. Consequently, education policy and practices in globally marginalised spaces (be it from the Global South, BRICS-nations or other postcolonial, low- and middle-income countries, emerging economy spaces) are not necessarily responsible or responsive – drawing on evidence irrelevant to specific socio-cultural and contextual resources and challenges. One reason put forward for the unevenness in the knowledge continuum is based on a view of limitations in the reporting of quality of studies from globally marginalised spaces. Metrics to evaluate the quality of research and thus merit for publication, also originates in the Global North. In this article the TAPESTRe framework is proposed as an instrument to plan for and evaluate the quality of studies from these underrepresented knowledge spaces – TAPESTRe: Transformative, emancipatory research; Agentic justice; Participatory approach; Emic place-sensitive; (geopolitical) Space; Trustworthiness criteria; Resilience outcomes. The TAPESTRe framework provides a complimentary framework to use as a quality appraisal tool to design, report and evaluate reporting on studies in underrepresented knowledge spaces as a means to mitigate the unequal, global evidence base which informs education policy and practice.